Pengaruh Model Pembelajaran Berbasis Masalah dengan Bantuan Komik Digital terhadap Kemampuan Literasi Ilmiah Siswa - Rini Rita T. Marpaung; Berti Yolida; Arrum Ardila Faros; Median Agus Priadi; Dina Maulina; Ismi Rakhmawati; Nadya Meriza; Laily Fatimatuzzahra; Yosi Fatmawati (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Background: The low scientific literacy of students is caused by the selection of models and learning media that are less varied. This study aims to analyze the effect of the PBL model with digital comics on students’ scientific literacy on environmental pollution material. Methods: This type of research is a quasi-experimental nonequivalent control group design. The research sample used classes, namely class VII A and VII F, with 55 students selected using a purposive sampling technique. Results: The experimental class's average N-Gain of scientific literacy ability (0.42 ± 0.171) is moderate, while the control class (0.26 ± 0.17) is low. Conclusions: The results of this study indicate that Sig. (2-tailed) 0.001 < 0.0, meaning that the PBL model using digital comics model cs influences students' scientific literacy skills.